Metformin associated lactic acidosis: a case series of 28 patients treated with sustained low-efficiency dialysis (SLED) and long-term follow-up - Andrea Angioi; Gianfranca Cabiddu; Maura Conti; Gianfranco Pili; Alice Atzeni; Valeria Matta; Riccardo Cao; Matteo Floris; Marco Songini; Maria Franca Mulas; Mitchell Rosner; Antonello Pani (BMC Nephrology, 2018)
Abstract Background Metformin associated lactic acidosis (MALA) is a well-known serious side effect of biguanides. However, the best treatment strategy remains a matter of debate. In the last 14 years, we observed a significant increase in hospitalizations for MALA to our Center. We report the outcomes of our clinical and therapeutic approach. Methods This is a single-center case series. Twenty-eight patients affected with MALA and acute kidney failure admitted between January 2000 and September 2014 were included. We analyzed comorbidities, laboratory tests and clinical parameters at admission, at 36 h and at discharge. All patients were treated with sustained low-efficiency dialysis (SLED) until normalization of serum lactate (≤ 3 mmol/L), bicarbonate (between 20 and 25 mmol/L) and potassium (between 4.0 and 5.1 mmol/L). Results The mortality rate was 21.4%, with all of the events occurring within 24 h from admission, and before or during the first hemodialysis treatment. Precipitating causes included; acute dehydration (86.4%), systemic inflammatory response syndrome (SIRS) (57.1%), sepsis (10.7%), nephrolithiasis (14.6%) and exposure to iodinated contrast (7.1%). No further episodes of lactic acidosis were described after discontinuing the drug over a mean follow-up of 27.2 months. Furthermore, while in 2010, we had a peak incidence of MALA of 76.8 cases per 100,000 patients on metformin, this rate fell after an education campaign conducted by specialists on the proper usage of metformin in patients at risk of MALA. Although the fall in incidence after the educational program was not necessarily causal, in 2014 the incidence was 32.9/100,000. Conclusions We report an improved mortality rate in patients affected with MALA and acute kidney injury treated with SLED compared with other series published in literature. Rapid introduction of effective hemodialysis is critical in improving outcomes.